The role of Carthago in the debate about the Phoenician-Punic human sacrifice - Kormikiari, Maria Cristina Nicolau (Romanitas - Revista de Estudos Grecolatinos, 2017)
The existence or not of human, child, sacrifice among the Phoenician-Punic peoples has been the subject of heated academic debates for more than a century. Recently, a significant body of revisions and new physico-chemical approaches, using the Carthaginian remains, have revived the issue, which has once again been at the heart of international replicas. Are we dealing with an issue that runs beyond our capacity for impartial analysis? This article intends to approach the most recently organized data in relation to the theme and the interpretations that follow. In this context, North Africa stands out as the only space, so far, where particularly thought-provoking archeological vestiges have been found. In addition to the central role that Carthage seems to have played, we have on North African soil the only known case of “export” of this complex ritual practice. We refer to the El-Hofra sanctuary in Cirta (modern Constantine, Algeria), a Numidian area with a strategic position in the region’s trading network, visited and inhabited by Greeks, Latins, Carthaginians, and the Berbers themselves.